(untitled) (Neo Scientific Peer Reviewed Journal, 2024)
This study explored the relationship between innovation policies and competitive advantage of manufacturing firms in Rivers state, Nigeria. It is believed that manufacturing firms in Rivers State struggles to achieve competitive advantage due to infrastructural deficit, inconsistent policy implementation and limited access to technologies and skills. More so, workers bureaucratic inefficiencies and corruption had also hindered the utilization of innovative policies which had led to suboptimal performance. To solve these problems, this research posited seven research objectives and its corresponding seven research hypotheses which were tested. It also examined how three dimensions of innovation policies (mission-oriented policies, innovation-oriented policies, and systems-oriented policies) influence two measures of competitive advantage (customer loyalty, and brand reputation), considering the moderating effect of firm’s size. A structured questionnaire was employed to collect primary data from 152 respondents across 7 manufacturing firms in Port Harcourt. Data was analysed using spearman rank order correlation coefficient. Out of the 152 study elements that constituted the population, 138 respondents were actually used. The study confirmed significant positive relationships between all three innovation policies dimensions and all two competitive advantage measures. Additionally, firm’s size was found to significantly moderate the relationship between innovation policies and competitive advantage. Innovation policies significantly enhance competitive advantage in Nigerian manufacturing firms. However, the strength of this relationship depended on the prevailing firm’s size. The study offered seven actionable recommendations for manufacturing firms to enable the implementation of mission-oriented policies, innovation-oriented policies, and systems-oriented policies, for the achievement of competitive advantage.